2018
DOI: 10.2136/vzj2018.06.0118
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Main Factors Contributing to the Spatial Variability of Soil Saline–Sodic Properties in a Reclaimed Coastal Area

Abstract: Citation: Citation: Fei, Y., D. She, and K. Fang. 2018. Identifying the main factors contributing to the spatial variability of soil saline-sodic properties in a reclaimed coastal area. Vadose Zone J. 17:180118.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Several papers in this special section address land use and management from a soil physical perspective. Using multiple regression techniques, Fei et al (2018) studied the controlling factors on soil salinity and alkalinity in a reclaimed coastal area of the Yellow Sea located in Jiangsu Province, China. They found that land use pattern (farmland vs. fallow), vegetation coverage, reclamation history, and soil texture significantly affected the soil salt content and the sodium adsorption ratio.…”
Section: This Special Sectionmentioning
confidence: 99%
“…Several papers in this special section address land use and management from a soil physical perspective. Using multiple regression techniques, Fei et al (2018) studied the controlling factors on soil salinity and alkalinity in a reclaimed coastal area of the Yellow Sea located in Jiangsu Province, China. They found that land use pattern (farmland vs. fallow), vegetation coverage, reclamation history, and soil texture significantly affected the soil salt content and the sodium adsorption ratio.…”
Section: This Special Sectionmentioning
confidence: 99%
“…The silt content had a significant positive correlation with soil salinity, but the sand content had a significant negative correlation with soil salinity [38]. Another study reported a significant positive correlation between soil salt content and sand content, but it was negatively correlated with the clay content [14]. We found that the TSC is significantly positively correlated with the silt content, but it is significantly negatively correlated with the clay content (Table 4).…”
Section: Soils Salinity Of the Different Soil Layers And Its Correlation With The Other Propertiesmentioning
confidence: 49%
“…In this study, soil texture (sand content, silt content, or clay content) was selected as the covariance in the cokriging prediction. This is mainly because the soil texture forms the basis of the soil structure and strongly affects the leaching of salt [14].…”
Section: Cokriging Interpolationmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate and prevent soil salinization, many conventional remediation methods had been investigated and applied, including soil substitution, soil drainage, irrigation, chemical amendments, and salt‐accumulating plants (Choi et al, 2012; Jo et al, 2015; Kim et al, 2011; Li et al, 2016; Yang et al, 2018). However, most are ineffective due to freshwater shortages (Fei et al, 2018; Liu et al, 2018), higher costs (Chen et al, 2015), longer reclamation times (Jo et al, 2012; Sun et al, 2017), or not being environmentally sustainable (Chen et al, 2019). Additionally, fine‐grained soil in coastal areas render the remediation work more difficult.…”
Section: Introductionmentioning
confidence: 99%